2021
DOI: 10.3389/fpsyg.2021.689184
|View full text |Cite
|
Sign up to set email alerts
|

Altruistic Giving Toward Refugees: Identifying Factors That Increase Citizens' Willingness to Help

Abstract: Over the past decade, the world has faced an unprecedented refugee crisis. The large number of incoming refugees represents a challenge for host societies and its citizens triggering reactions from a supportive welcome to brusque rejection and hostile behavior toward refugees. In a pre-registered study, we investigated factors that could promote altruistic behavior in fully incentivized one-shot Dictator Game toward various receiver groups including refugees. We find that host citizens behave more altruistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 126 publications
1
9
0
Order By: Relevance
“…It has repeatedly been shown that prosocial behavior depends on characteristics of the giver, the recipient, and their interpersonal relation. For instance, cross-cultural studies report that prosocial behavior depends on the individuals' social and political orientation (i.e., characteristic of the giver; Hellmann et al, 2021), the recipients' national background (i.e., characteristic of the recipient; Fiedler et al, 2018) or the similarity between givers and recipients (i.e., interpersonal characteristic; Froehlich et al, 2021). Furthermore, it has been shown that prosocial behavior increases with the recipient's socio-economic vulnerability in relation to the giver (economic inequality; Dorrough & Glöckner, 2016) and decreases with psychological distance towards (unidentified) recipients (Kogut et al, 2018), which can both be considered interpersonal characteristics.…”
Section: Pandemic-specific Context Factors Associated With Prosocial Behaviormentioning
confidence: 99%
“…It has repeatedly been shown that prosocial behavior depends on characteristics of the giver, the recipient, and their interpersonal relation. For instance, cross-cultural studies report that prosocial behavior depends on the individuals' social and political orientation (i.e., characteristic of the giver; Hellmann et al, 2021), the recipients' national background (i.e., characteristic of the recipient; Fiedler et al, 2018) or the similarity between givers and recipients (i.e., interpersonal characteristic; Froehlich et al, 2021). Furthermore, it has been shown that prosocial behavior increases with the recipient's socio-economic vulnerability in relation to the giver (economic inequality; Dorrough & Glöckner, 2016) and decreases with psychological distance towards (unidentified) recipients (Kogut et al, 2018), which can both be considered interpersonal characteristics.…”
Section: Pandemic-specific Context Factors Associated With Prosocial Behaviormentioning
confidence: 99%
“…Similarly, Hellmann et al. (2021) found that when participants were asked to allocate money between themselves and different groups, perceived closeness was positively associated with donations towards refugees, and De Coninck (2020) found that when asked which groups of immigrants should be allowed to come and live in the country, people were more positive towards European than non‐European refugees. Finally, when examining prejudice against different groups, with samples from four European countries, Bruneau et al.…”
Section: Introductionmentioning
confidence: 96%
“…In a field experiment conducted in Switzerland, Zhang et al (2019) found that an immigrant who was less fluent in German was perceived as being of lower status and was less likely to receive help when asking to borrow a telephone. Similarly, Hellmann et al (2021) found that when participants were asked to allocate money between themselves and different groups, perceived closeness was positively associated with donations towards refugees, and De Coninck (2020) found that when asked which groups of immigrants should be allowed to come and live in the country, people were more positive towards European than non-European refugees. Finally, when examining prejudice against different groups, with samples from four European countries, Bruneau et al (2018) found that Muslim refugees were among the most dehumanized groups.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations